From Perception to Communication A Theory of Types for Action and Meaning - Cooper, Robin (Oxford University Press, 2023)
The aim of this book is to characterize a notion of type which will cover both linguistic and non-linguistic action and to lay the foundations for a theory of action based on a theory of types called TTR (a Theory of Types with Records). The book argues that a theory of language based on action allows us to take a perspective on linguistic content which is centred on interaction in dialogue and that this is importantly different to the traditional view of natural languages as being essentially similar to formal languages such as logics developed by philosophers or mathematicians. At the same time it will argue that the tremendous technical advances made by the formal language view of semantics can be incorporated into the action-based view and that this can lead to important improvements both of intuitive understanding and empirical coverage. In this enterprise we use types rather than possible worlds as commonly employed in studies of the semantics of natural language. Types are more tractable than possible worlds and give us more hope of understanding the implementation of semantics both on machines and in biological brains.